Série Chapeuzinho Vermelho de Francisco Brennand: discurso da arte e representações do corpo feminino. - Cavalcanti, Cristiane Renata da Silva (2019)
This work is part of a recent research movement in French Speech Analysis (AD) that investigates artistic discourse. His objective was to analyze how the effects of senses of the series Little Red Riding Hood by the artist Pernambuco Francisco Brennand constitute. Our study thus proposes to analyze the discourse that is inscribed in the field of art as discourse, marked by a place of saying of history and ideology, considering the notion of body as a discursive materiality, as well as art, situating them between the language and the subject, constitutive of meanings. Our corpus consisted of 40 screens from the series entitled Little Red Riding Hood by the artist from Pernambuco, Francisco Brennand, in order to analyze the plots of possible meanings that are realized in these speeches and the gestures of interpretation that are established in the works of the artist, making possible new words. In order to do so, our reflection was based on the observation of the discursive functioning of the series, on the process of producing meanings in the face of the influence of exteriority on the constitution of the discursive and ideological formations that are marked in the discourse of the series; the way in which the functioning of discursive memory implies senses in it and in what way the notion of body can be explored in these, in order to seek the understanding of how these discourses function and produce meanings. Our objective is to understand and analyze the way in which the effects of senses of the series are constituted and we intend to understand the discursive relation of the image through the specific objectives: To observe the possible discursive formation in the series functioning; Consider how the discursive memory implies the signification of the senses, through the paraphrastic and polysemic movements and Analyze the discourse of the body in the works of the plastic artist from Pernambuco. Resulting, in this way, in the possible gestures of interpretation of the image body and its imaginary formations regarding the female body and its representations. In addition, we observe that the work presupposes the perennial incompleteness of the facts of the language, understanding that the saying will always be point of drift towards other senses. This allows us to affirm that the process of production of the senses of the screens, by its verbal-visual nature, occurs from the relation between its immediate conditions of production and the interdiscourse, constitutive elements of the discourse. Thus, through the recollection of facts and discourses, materialized in the images, we believe that this research contributes to reflect on the importance of the mobilization of memory that intervenes in the production of meanings on the screen, articulating AD and art.